New Fluorescence Quenching Approach for Determination of Valsartan in Certain Tablets and Spiked Biological Fluids - Abd Ali, Layth I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
A new, simple, selective, sensitive, fast, economical, and reliable fluorescence quenching method for the quantitation of valsartan was investigated using basic fuchsin act as a fluorometric dye. The method was depended on the detection quenching influence of valsartan on the fluorescence intensity of basic fuchsin and the reaction between valsartan and basic fuchsin in a McIlvaine buffer medium at pH = 6 to yield a new basic fuchsin–valsartan non-fluorescent complex. The excitation and emission of basic fuchsin fluorescence signal were identified at 535 and 728 nm, respectively. A fluorescence quenching value (ΔF) displayed a very good linear relationship (R2 = 0.9992) with valsartan concentration ranging from 0.003 to 3 μg/mL, a detection limit as low as 0.0009 μg/mL with a high precision and accuracy (RSD% <3). Significantly, no interference effect was found due to the presence of other ingredients commonly found in medical formulations. The acquired data were statistically compared with those acquired from reported chromatographic method and were observed to be in excellent agreement at a 95% confidence level; the planned fluorescence quenching procedure was subsequently utilized to detected the concentration of valsartan in spiked biological fluids and commercial medical tablets.